Horizontal Building Separation Based on Government Regulation Number 16 of 2021 concerning Fiduciary Guarantees in Medan City - Lilawati Ginting; Onny Medaline; Ida Hanifah (Faculty of Law, Universitas Pekalongan, 2025)
This study examines the implementation of the horizontal separation principle in the regulation of buildings as objects of fiduciary collateral based on Government Regulation No. 16 of 2021, with a study focus on the City of Medan. This principle allows buildings to be used as fiduciary collateral without having to pledge the land on which the building stands, thus opening up new access to credit facilities. However, the implementation of this principle still faces various obstacles, including low understanding from business actors and financing institutions, as well as limitations in the administrative system and socialization of regulations. The results of the study show that although the Building Ownership Certificate (SBKBG) has been regulated as the legal basis for fiduciary imposition on buildings, its implementation is still not optimal due to limited supporting infrastructure and technical regulations for implementation. This study emphasizes the importance of strengthening socialization, harmonization of regulations, and the readiness of related institutions to ensure legal certainty and the effectiveness of the implementation of the horizontal separation principle in supporting the development of the fiduciary guarantee system. These findings are expected to contribute to the formulation of more inclusive and responsive policies in supporting the property financing sector in Indonesia.